Addressing Disparities in Clean and Healthy Living Behaviors through Targeted Health Education in a Rural Community - Irianiwati Widodo; Hanggoro Tri Rinonce; Azzahra Asysyifa; Cut Alima Syarifa; Aflifia Birruni Sabila; Bira Arumndari Nurrahma; Arta Farmawati; Dwi Cahyani Ratna Sari; Dwi Aris Agung Nugrahaningsih; Sudi Indra Jaya; Eti Nurwening Sholikhah; Dicky Moch Rizal; Rina Susilowati; Titik Nuryastuti; E. Elsa Herdiana Murhandarwati; Teguh Triyono; Tri Ratnaningsih (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: This study addresses the public health issue of community hygiene and wellness by focusing on the Clean and Healthy Lifestyle Behavior (CHLB) as a key parameter. The subject of the assessment is the community of Sompok Hamlet, Bantul, with the purpose of evaluating the implementation of CHLB within households to understand areas of strength and needed improvement. Purpose of the Study: The purpose is to assess the level of CHLB implementation in Sompok Hamlet. The objective is to measure household compliance across various CHLB indicators and identify specific behavioral gaps that require targeted intervention. Methods: The study employed a cross-sectional survey design conducted in 2023. Data were collected from 202 households across seven neighborhood units (RT) using a structured questionnaire to evaluate compliance with standard CHLB indicators. Results: The results showed that 68.3% of households met the criteria for independent healthy communities. High compliance was observed in indicators like access to clean water, sanitation, exclusive breastfeeding, and toddler weighing. However, significant gaps were identified in physical activity (71.3% low compliance) and indoor smoking practices (64% low compliance). Practices related to fruit/vegetable consumption, handwashing, and larva elimination showed varied results. The findings highlight the need for focused educational programs to address these specific behavioral deficiencies to promote sustainable community health.